2021
DOI: 10.3390/jof7090690
|View full text |Cite
|
Sign up to set email alerts
|

Adapting an Ergosterol Extraction Method with Marine Yeasts for the Quantification of Oceanic Fungal Biomass

Abstract: Ergosterol has traditionally been used as a proxy to estimate fungal biomass as it is almost exclusively found in fungal lipid membranes. Ergosterol determination has been mostly used for fungal samples from terrestrial, freshwater, salt marsh- and mangrove-dominated environments or to describe fungal degradation of plant matter. In the open ocean, however, the expected concentrations of ergosterol are orders of magnitude lower than in terrestrial or macrophyte-dominated coastal systems. Consequently, the fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In order to have fresh cultures, the pure isolates were cultured on yeast malt extract agar [ 23 , 24 ] for one week. Afterwards, an initial amount of each fungus was diluted in artificial seawater (30 g/L sea salts S9883 Sigma-Aldrich, Vienna, Austria) to obtain an OD 660 ≈ 1 [ 25 ]. The optical density (OD) was measured with a UV-1800 Shimadzu spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…In order to have fresh cultures, the pure isolates were cultured on yeast malt extract agar [ 23 , 24 ] for one week. Afterwards, an initial amount of each fungus was diluted in artificial seawater (30 g/L sea salts S9883 Sigma-Aldrich, Vienna, Austria) to obtain an OD 660 ≈ 1 [ 25 ]. The optical density (OD) was measured with a UV-1800 Shimadzu spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…A biphasic layer is formed upon extraction, with lipids contained in the chloroform layer and non-lipid compounds within the Milli-Q water aqueous layer. Alekseyeva et al [18] experimentally showed the presence of 98 % of the total extracted ergosterol was present within the chloroform layer. Both the present study and Alekseyeva et al [18] dried the extracts upon completion before reconstituting in methanol.…”
Section: Discussionmentioning
confidence: 99%
“…The use of methanol alone for the extraction of ergosterol has been utilized by several investigations with a range of success [18,23,24]. The main difference in methanol alone to extract ergosterol is the duration of a heat treatment in a water bath or heating block dependent on the overall volume of the sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations